Antifungal diastereomeric furanones from Mutisia friesiana: structural determination and conformational analysis - Viturro, Carmen Ines (2001)
Two diastereomeric furanones, (4S,5S)-5-(4-methyl-3-pentenyl)-4-hydroxy-5-methyldihydrofuran-2-one 1 and (4S,5R)-5-(4-methyl-3-pentenyl)-4-hydroxy-5-methyldihydrofuran-2-one 2 were isolated for the first time from the shrub Mutisia friesiana. The relative stereochemistries of 1 and 2 were ascertained from NOESY NMR data and confirmed by a combination of molecular modeling (molecular mechanics and ab initio molecular orbital calculations) and NMR data. Comparison between experimentaland calculated 1H?1H vicinal coupling constants revealed that both furanones exist in an equilibrium of two stable conformers of the five-membered ring. Application of Mosher?s method suggests that both diastereomeric furanones have the same (S)-configuration at C-(4) and are epimers at C-(5). Furanones 1 and 2 showed antifungal activity against the pathogenic fungus Cladosporium cucumerinum.